2008
DOI: 10.1017/s1041610208007394
|View full text |Cite
|
Sign up to set email alerts
|

Screening for dementia in primary care: a review of the use, efficacy and quality of measures

Abstract: Although the MMSE is widely used in the U.K., this project identifies the GPCOG, MIS and Mini-Cog as clinically and psychometrically robust and more appropriate for routine use in primary care. A coherent review of evidence coupled with an indepth evaluation of screening instruments has the potential to enhance ability and commitment to early intervention in primary care and, as part of a wider educational strategy, improve the quality and consistency of dementia screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
145
1
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(154 citation statements)
references
References 49 publications
0
145
1
8
Order By: Relevance
“…However, this can take up to 20 min to complete and may not be practical for use in primary care. The General Practitioner Assessment of Cognition (primary care physician COG) (Brodaty et al, 2002), and two other cognitive screening tests, the Mini-Cog Assessment Instrument (Borson et al, 2000) and the Memory Impairment Screen (MIS) (Buschke et al, 1999), have been found to be as clinically and psychometrically robust and more appropriate for use in primary care than the MMSE (Milne et al, 2008). The primary care physician COG is estimated to take 5-7 min to complete with questions for both the patient and family carer, and thus may be more relevant for primary care physicians (Brodaty et al, 2002).…”
Section: Assessment Of Cognitive Functionmentioning
confidence: 99%
“…However, this can take up to 20 min to complete and may not be practical for use in primary care. The General Practitioner Assessment of Cognition (primary care physician COG) (Brodaty et al, 2002), and two other cognitive screening tests, the Mini-Cog Assessment Instrument (Borson et al, 2000) and the Memory Impairment Screen (MIS) (Buschke et al, 1999), have been found to be as clinically and psychometrically robust and more appropriate for use in primary care than the MMSE (Milne et al, 2008). The primary care physician COG is estimated to take 5-7 min to complete with questions for both the patient and family carer, and thus may be more relevant for primary care physicians (Brodaty et al, 2002).…”
Section: Assessment Of Cognitive Functionmentioning
confidence: 99%
“…A quick glance through an issue of International Psychogeriatrics pulled from my shelves at random (20 (5), October 2008), revealed that of 16 review or original research articles, five (31%) (Lyketsos et al, 2008;Mendes-Chiloff et al, 2008;Milne et al, 2008;Nakaaki et al, 2008;Orrell et al, 2008) cited Folstein's MMSE. It therefore caused me little surprise to find that that the valuable contribution of Han et al (2000) in establishing a typical rate of decline for AD patients assessed with the MMSE had received the equal sixth highest number of citations of any paper published in the journal up to the end of 2006.…”
Section: Commentarymentioning
confidence: 99%
“…Because damage caused by the pathophysiologic mechanisms associated with AD is presumed to be irreversible, early detection of AD offers better prospects for patients with AD and their families and friends. This allows both the patient and family to participate in their care plan and to prepare better for future challenges as a result of the neurodegenerative process 26,27 because currently available medications, and any future disease-modifying agents, will have the greatest opportunity for providing benefit. In addition, recent evidence suggests that early treatment provides economic benefits both to the patient and caregiver as well as society as a whole.…”
Section: Importance and Challenges Of Early Diagnosismentioning
confidence: 99%
“…Both have psychometric properties superior to the MMSE; as such, they are clinically and psychometrically robust and, it has been argued, are more appropriate for routine use in primary care. 27,46 Step 3: Assessment of Daily Functioning An assessment of daily function is vital to determine the extent of the patient's disability and dependence on the caregiver, the results of which help to enable planning to maximize patients' independence. 47 Basic ADLs, such as feeding and toileting, can be assessed with an interview or by using a tool such as the ADL Scale.…”
Section: Informant-based Screening Toolsmentioning
confidence: 99%